Ask Question
17 April, 07:13

If (2x+a) (2x+b) = 4x^2-4x+ab, then a+b = ?

A. - 4

B. - 2

C. - 1

D. 2

E. 4

+3
Answers (1)
  1. 17 April, 09:03
    0
    Answer: a+b = - 2

    B. - 2

    Because if a = 1 and b = - 3 then

    (2x+a) (2x+b) = 4x^2-4x+ab

    Plug in a = 1 and b = - 3 into (2x+a) (2x+b) then solve

    (2x+a) (2x+b)

    = (2x + 1) (2x - 3)

    = 4x^2 + 2x - 6x - 3

    = 4x^2 - 4x - 3 (so ab = - 3)
Know the Answer?
Not Sure About the Answer?
Get an answer to your question ✅ “If (2x+a) (2x+b) = 4x^2-4x+ab, then a+b = ? A. - 4 B. - 2 C. - 1 D. 2 E. 4 ...” in 📙 Mathematics if there is no answer or all answers are wrong, use a search bar and try to find the answer among similar questions.
Search for Other Answers